Neurologic involvement in patients with atypical Chediak-Higashi disease. (14th February 2017) - Introne, Wendy J.; Westbroek, Wendy; Groden, Catherine A.; Bhambhani, Vikas; Golas, Gretchen A.; Baker, Eva H.; Lehky, Tanya J.; Snow, Joseph; Ziegler, Shira G.; Malicdan, May Christine V.; Adams, David R.; Dorward, Heidi M.; et al.
Abstract : Objective: To delineate the developmental and progressive neurodegenerative features in 9 young adults with the atypical form of Chediak-Higashi disease (CHD) enrolled in a natural history study. Methods: Patients with atypical clinical features, but diagnostically confirmed CHD by standard evaluation of blood smears and molecular genotyping, underwent complete neurologic evaluation, MRI of the brain, electrophysiologic examination, and neuropsychological testing. Fibroblasts were collected to investigate the cellular phenotype and correlation with the clinical presentation. Results: In 9 mildly affected patients with CHD, we documented learning and behavioral difficulties along with developmental structural abnormalities of the cerebellum and posterior fossa, which are apparent early in childhood. A range of progressive neurologic problems emerge in early adulthood, including cerebellar deficits, polyneuropathies, spasticity, cognitive decline, and parkinsonism. Conclusions: Patients with undiagnosed atypical CHD manifesting some of these wide-ranging yet nonspecific neurologic complaints may reside in general and specialty neurology clinics. The absence of the typical bleeding or infectious diathesis in mildly affected patients with CHD renders them difficult to diagnose. Identification of these individuals is important not only for close surveillance of potential CHD-related systemic complications but also for a full understanding of the natural history of CHD and the potential role of the disease-causing protein, LYST, to the pathophysiology of other neurodevelopmental and neurodegenerative disorders.